How does an Ethiopian dam increase malaria?: entomological determinants around the Koka Reservoir - Kibret, Solomon; Lautze, Jonathan F.; Boelee, Eline; McCartney, Matthew P. (Wiley, 2012)
The aim of the study was to identify entomological determinants of increased malaria transmission in the vicinity of the Koka reservoir in Central Ethiopia. Larval and adult mosquitoes were collected between August 2006 and December 2007 in villages close to (<1 km) and farther away from (>6 km) the Koka reservoir. Adult mosquitoes were tested for the source of blood meal and sporozoites. In reservoir villages, shoreline puddles and seepage at the base of the dam were the most productive Anopheles-breeding habitats. In villages farther from the dam (control villages), rain pools were important breeding habitats. About five times more mature anopheline larvae and six times more adult anophelines were found in the villages near the reservoir. Anopheles arabiensis and Anopheles pharoensis were the most abundant species in the reservoir villages throughout the study period. The majority of adult and larval anophelines were collected during the peak malaria transmission season (September?October). Blood meal tests suggested that A. arabiensis fed on humans more commonly (74.6%) than A. pharoensis (62.3%). Plasmodium falciparum-infected A. arabiensis (0.97?1.32%) and A. pharoensis (0.47?0.70%) were present in the reservoir villages. No P. falciparum-infected anophelines were present in the control villages. The Koka reservoir contributes to increased numbers of productive Anopheles-breeding sites. This is the likely the cause for the greater abundance of malaria vectors and higher number of malaria cases evidenced in the reservoir villages. Complementing current malaria control strategies with source reduction interventions should be considered to reduce malaria in the vicinity of the reservoir.